Media Fragmentation - Issues and Challenges - Selvabaskar, S. (Indian Journal of Marketing, 2007)
In recent years, the Indian Market is witnessing a cutthroat competition in various market segments. Right from FMCGs to Automobiles, the cold war between the various brands is so evident and importantly it keeps mounting from time to time. In such an environment, the ultimate winner is the one who succeeds in acquiring a considerable mind share through effective; marketing communication. Thus, the focus is very much on the promotional tools; where the decisions on the promotion-mix are found to be imperative. "Advertising" is considered to be an important element of Promotion-Mix. The Indian Advertising Industry is back to its growth track and has been growing steadily over the years. Though factors like competition, new players in the market, business growth, etc., are cited as some of the reasons, one can’t reject the fact that media fragmentation has contributed a lot towards its growth. This has opened up the doors for small, niche players to effectively participate in the battle. This fragmentation process is blanketed across all media like Print, Television, Broadcasting, etc.